Pengaruh Metode Problem Based Learing terhadap Peningkatan Hasil Belajar dalam Pembelajaran Pendidikan Agama Islam kelas V di SDN Sukawening - Nina Destiani; Dera Nugraha; Alfa Rohmatin (Al-Khazin: Jurnal Pendidikan Agama Islam, 2026)
Learning outcomes in Islamic Religious Education still require serious attention because teacher-centered instruction often limits students’ active participation and conceptual understanding. This study aimed to determine the effect of the Problem Based Learning method on improving the learning outcomes of fifth-grade students in Islamic Religious Education at SDN Sukawening. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research sample consisted of 38 fifth-grade students selected through saturated sampling. Data were collected using multiple-choice tests administered before and after the implementation of Problem Based Learning. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the paired sample t-test. The results showed that the mean pretest score was 6.50, while the mean posttest score increased to 9.05. The paired sample t-test produced a significance value of 0.000, which was lower than 0.05. These findings indicate a significant difference between students’ learning outcomes before and after the implementation of Problem Based Learning. Therefore, Problem Based Learning has a significant effect on improving students’ learning outcomes in Islamic Religious Education. This method can support more active, contextual, and meaningful learning in elementary school.